2021
DOI: 10.1177/15579883211011371
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Efficacy of L-Carnitine/L-Acetyl-Carnitine or N-Acetyl-Cysteine in Men With Idiopathic Asthenozoospermia

Abstract: The meta-analysis was performed to access efficacy of L-carnitine/L-acetyl-carnitine (LC/LAC) and N-acetyl-cysteine (NAC) in men with idiopathic asthenozoospermia. We researched PubMed, EMBASE, and Cochrane Library databases and references to related articles. Finally, seven articles including 621 patients were analyzed. The results indicated that LC/LAC and NAC had a considerable improvement in sperm motility ( p = .03 and p < .0001, respectively) and normal morphology ( p = .006, p = .0002, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…Compared to the last Cochrane review [ 14 ], the present study increased the number of RCTs, allowing the study of the largest population analyzed so far ( Table 3 ). This allowed us to confirm the Cochrane’s study findings and upgrade the level of evidence of many of the investigated outcomes [ 14 75 89 90 91 ] ( Table 3 ). Moreover, to the best of our knowledge, this is the first study to offer a meta-analytic investigation of seminal levels of TAC and MDA in patients with male infertility after AOX administration and to confirm a positive effect on both of these outcomes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Compared to the last Cochrane review [ 14 ], the present study increased the number of RCTs, allowing the study of the largest population analyzed so far ( Table 3 ). This allowed us to confirm the Cochrane’s study findings and upgrade the level of evidence of many of the investigated outcomes [ 14 75 89 90 91 ] ( Table 3 ). Moreover, to the best of our knowledge, this is the first study to offer a meta-analytic investigation of seminal levels of TAC and MDA in patients with male infertility after AOX administration and to confirm a positive effect on both of these outcomes.…”
Section: Discussionsupporting
confidence: 56%
“…Studies on single supplements or on specific clinical contexts have demonstrated the positive role of AOXs on semen quality and reproductive outcomes. Thus, two recent meta-analyses of RCTs showed a significant positive effect of NAC and L-carnitine/L-acetyl-carnitine (LC/LAC) on semen parameters [ 17 18 ]. In addition, a meta-analysis of six studies with a total of 576 patients, found that the administration of AOXs after varicocelectomy resulted in a greater improvement in sperm concentration (p<0.0001), total sperm motility (p=0.03), progressive sperm motility (p<0.00001), and sperm morphology (p<0.00001) compared to placebo [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were small scale, and although some combinations did demonstrate an improvement in semen parameters, the differences tended to be small, and no studies demonstrated a significant difference in pregnancy rates. The antioxidant combinations, which showed improvement in sperm parameters include CoQ10 [11 ▪ ,12 ▪ ], l -carnitine, N-acetyl-cysteine [13 ▪ ,14 ▪ ,15 ▪ ,16 ▪ ,17], and vitamin D [18 ▪ ].…”
Section: Medical Treatmentsmentioning
confidence: 99%
“…33 El tratamiento con L-carnitina por 3 meses produjo mejoría significativa en la concentración, motilidad velocidad en línea recta, velocidad curvilínea y velocidad promedio en 78% de los pacientes. 34 Varios estudios informan correlación positiva y significativa entre las concentraciones de L-carnitina y la supervivencia y motilidad de los espermatozoides en el moco cervical. En este medio, los lípidos son la fuente de energía y para metabolizarlos la L-carnitina intracelular es fundamental.…”
Section: L-carnitinaunclassified